Apexogenesis of traumatized maxillary right central incisor: Case report with 4years follow up - Hammo DDS, Mohammad; Doumani DDS. MSc., Mazen; Habib DDS. MSc. PhD, Adnan (International Journal of Dental Research, 2019)
The main goal of vital pulp therapy is to preserve and maintain pulpal health in teeth that have been exposed to caries, trauma, and restorative procedures. This type of endodontic treatment is very important in young permanent teeth that have not reached their complete length and exhibit thin-walled roots and wide open apices. The developments in knowledge of pulpal physiology and immunology, beside to newly introduced dental materials, have changed the treatment approaches for teeth with involved pulps. This report describes a case of a young patient in whom maxillary right central incisor suffered crown fractures because of a traumatic accident. Pulpotomy with MTA were performed in order to achieve apexogenesis and the tooth was restored with a glass ionomer cement and composite resin. The patient was reviewed over 4years.Â